Ignition characteristics of H2-air mixtures with hot particles - Nupur Gupta; Rohit Kumar; Jithin Edacheri Veetil; Sudarshan Kumar; Ratna Kishore Velamati (Case Studies in Thermal Engineering)
Thermal ignition of fuel-air mixtures due to hot particles can pose security risks and be hazardous under various circumstances, leading to their auto-ignition. The ignition characteristics of hydrogen-air mixtures with hot particles were investigated by performing 2-D numerical simulations using a detailed H2-air kinetic model. The simulations were performed with hot particles of various sizes and shapes with hydraulic diameters of 2, 4, and 6 mm. The effect of particle surface temperature on the ignition characteristics was studied by performing simulations at various particle surface temperatures ranging from 1000 to 1200 K. The results showed that for different particle shapes and sizes, the ignition delay depends strongly on the particle temperature. The location of the ignition point depends on the particle shape and temperature. A particle with a temperature of 1200 K ignites at the front stagnation point. The behavior significantly differs at 1000 K as the ignition location is shifted to a different point due to a competition between reaction kinetics and flow around the hot particles. Spherical particle showed the highest heat release rate compared to other particle shapes.